Da ironia à seriedade: sobre o tornar-se indivíduo segundo Kierkegaard - Silva, Cássio Robson Alves da (2016)
Whereas the philosophy raises problems and works, for times, anchored in the field of possibilities, it becomes necessary the consistent use of any methodology or dialectic taht aimed the realization of the postulated hypotheses. For Søren Kierkegaard (1813-1855) is no different. Thus, this work has as a fundamental principle to show that his enterprise had been able to establish an open dialogue with the philosophical tradition and raise categories that may think both the most intimate questions of the individual as well as the reality that surrounds him. Therefore, based predominantly in the period 1841-1846 (mainly aesthetic Kierkegaard's works), will launch hand of fundamental concepts such as irony, time (instant) and authenticity / seriouness, understanding these as axis that here will call it – individual becomes. Faced with this challenge, as a start-ing point, we find in the works The Concept of Irony (1841), Either/Or - A fragment of life (1843), The Concept of Anxiety (1844) a conceptual proximity that allows we enter in the individual's relationship with time whose seriousness is therefore existential re-sult, the estimated result, and therefore, the condition of its engagement on the world and of itself. Three Discourses on imagined occasions (1845) will allow us to understand the work of Kierkegaard in a global way, especially if interspersed with Concluding Unscientific Postscript to Philosophical Fragments (1846), works without which the latter undertaking would not be possible.